INNOVATIVE METHODS FOR ASSESSING INDEPENDENT LEARNING IN MUSIC EDUCATION - Bobokulova Moxinur Jamshid qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores innovative methods for assessing independent learning in music education. It examines how contemporary digital tools, interactive platforms, and project-based activities can be used to evaluate students’ knowledge, technical skills, and creative abilities. The study highlights the effectiveness of self-assessment, peer assessment, and technology-mediated evaluation in promoting reflective practice and improving learning outcomes. Innovative assessment strategies not only measure performance but also support the development of critical thinking, self-directed learning, and professional competencies in music students.